Micro-Engagements through AI-Smartwatch Wearables for eHealth: User Experiential Discourses on Social Media - Ireen Mmatlou Manyuha; Elizabeth Lubinga (The Thinker, 2025)
Globally, the use of Artificial Intelligence (AI) wearables including smartwatches has gained traction. AI-Smartwatches have emerged as powerful communication tools and their increased use for personal eHealth is driven by capabilities to facilitate micro-engagements with users. Micro-engagements enhance user experience and active interaction by providing real-time feedback that triggers the user to act. While smartwatches have the potential to effectively drive positive user health behaviour through instant communication, it is imperative to examine the strategic use of communication of these devices by smartwatch users. The purpose of this study was to examine AISmartwatch user experiences, specifically micro-engagement perceptions. Theoretically, the study was underpinned by The Unified Theory of Acceptance and Use of Technology. A qualitative approach, using a netnography design provided results from online discourses expressed on X (formerly known as Twitter), in response to a question tweeted about the effectiveness of smartwatches. Results indicate that the use of AI-smartwatches has propelled active personal engagement with health. Users reported tracking various aspects of their health due to instantly available data that is in turn used to seek solutions from health professionals. Conversely, it is unclear whether lay people who are not health professionals are skilled in interpreting the instant data that they are exposed to. This study provides much-needed insight into user experiences of strategic use of communication through AI-powered smartwatch devices using data-driven micro-engagements. It will inform Health Professionals, Health Service Organisations and AI Technology Developers among others regarding practice as well as improvement of technological services for digital public health.